Particle size effect of raw material on the pore structure of carbon support and its adsorption capability. (4th May 2017) - Erdoğan, Selim; Akmil Başar, Canan; Önal, Yunus
ABSTRACT: In this study, a series of activated carbons were prepared from Tuncbilek lignite with different particle size by chemical activation. The effect of particle size of lignite on the pore structure of activated carbon and the adsorption kinetics of crystal violet (CV) onto these activated carbons was investigated. BET surface area values of activated carbon samples were determined in the range of 940–1054 m 2 g −1 . Adsorption capacity of CV onto activated carbons was investigated in a batch system by considering the effects of various parameters such as initial dye concentration, agitation time and adsorption temperature. The Langmuir and Freundlich isotherms were used to describe the adsorption equilibrium studies. The adsorption kinetics of CV has been discussed using the pseudo-first-order, pseudo-second-order and intraparticle diffusion models. Results show that the pseudo-second-order kinetic equation could describe the adsorption kinetics for CV onto activated carbons. Using the thermodynamic equilibrium coefficient obtained at different temperatures and for the initial dye, the thermodynamic constants of adsorption (Δ G °, Δ H ° and Δ S °) were also evaluated.